2014
DOI: 10.1007/s00217-014-2228-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient purification of cryoprotective dehydrin protein from the radish (Raphanus sativus) taproot

Abstract: Dehydrin is a protein that is related to cold stress tolerance in plants. Because dehydrin shows potent cryoprotective activity, it has the potential to be used in food storage applications. In this paper, we presented an efficient purification method for native dehydrin from radishes (Raphanus sativus). Immunoblot analysis using an anti-Arabidopsis KS type dehydrin antibody revealed that the related dehydrin accumulates in the radish taproot. The radish dehydrin that accumulated in the vascular tissues of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In addition to enzyme protection, other in vitro studies highlight multiple roles for dehydrins, including the protection of membranes and DNA [ 27 , 30 , 40 , 41 ], where the K-segment plays an important role. With regard to membranes, several studies have also shown that the K-segments in dehydrin gain α-helical structure in the presence of membranes [ 42 , 43 , 44 ], and that they are able to protect membranes from abiotic stresses [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to enzyme protection, other in vitro studies highlight multiple roles for dehydrins, including the protection of membranes and DNA [ 27 , 30 , 40 , 41 ], where the K-segment plays an important role. With regard to membranes, several studies have also shown that the K-segments in dehydrin gain α-helical structure in the presence of membranes [ 42 , 43 , 44 ], and that they are able to protect membranes from abiotic stresses [ 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%